Nerolidol-Loaded Graphene Oxide/Iron Nitrate/Nickel Nitrate Nanoparticles Induce Oxidative Stress-Mediated Apoptosis in Ovarian Cancer A2780 Cells - Jingjing Li; Wei Chen; Cuiling Gao (Journal of Pharmaceutical Innovation, 2026)

Prediction of honey adulteration using machine learning-assisted OIRD - Shanzhe Zhang; Shunyi Li; Hao Yang; Enhao Tang; Xiaorong Sun; Yuan Gao; Cuiling Liu; Kun Zhao (Food Bioscience, 2026)

Integrated detection and recovery of light/medium rare earth elements using Hans-LanM-based fluorescent probe and whole-cell adsorbent - Qunfang Li; You Wang; Cuiling Zeng; Zixin Wu; Wenqiang Chen; Dan Wang (Journal of Hazardous Materials, 2026)

Experimental and numerical investigation on structural damping behavior of corroded Fe-SMA - Yuanmu Li; Zhe-Xi Zhang; Cheng Fang; Guohui Cao; Cuiling Ran; Haihui Ren; Yuelin Zhang (Engineering Structures, 2026)

Environmental effects of Shenhu gas hydrate trial production: A perspective on carbon cycling in shallow sediments - Taiheng Lv; Cuiling Xu; Zhilei Sun; Hong Cao; Xilin Zhang; Wei Geng; Ye Chen; Sinan Xu; Dong Zhang; Yucheng Zhou; Shixing Li; Yunbao Sun; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

High-efficiency restoration of stone cultural relics via immobilized carbonic anhydrase on magnetic graphite oxide - Yaofeng Hu; Yifan Gui; Wei Li; Cuiling Gong; Ziqi Hou; Tong Shu; Ya Wu; Gen Lu; Longjiang Yu (Bioresource Technology, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Virtual screening of salty peptides from enzymatic and fermented products of wheat gluten and its molecular mechanism of interaction with TMC4 receptor - Haowen Chen; Huiyan Zhao; Jiarou Chen; Chunxia Zhou; Cuiling Li; Jianxu Chen; Jingjing Guan; Yongtai Wei; Guili Jiang; Donghui Luo (Food Chemistry, 2025)

Nationwide occurrence of emerging benzophenone, benzotriazole, salicylate and triazine ultraviolet filters in coastal sediment of China: Spatial distribution, source and ecological risk - Zhao Tang; Zilan Wu; Xuan Jia; Xing Liu; Xiaodan Pei; Zehua Liu; Xingan Xiong; Jianzhong Li; Xi Liu; Cuiling Wu; Ziwei Yao (Environmental Research, 2025)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Combined transcriptome and metabolome analyses provide insights into host adaptation mechanism of Spodoptera frugiperda to cruciferous vegetables - Benshui Shu; Yuning Li; Cuiting Liu; Junying Wu; Cuiling Ye; Jintian Lin; Jingjing Zhang (Journal of Insect Physiology, 2025)

Genomic insights into the genetic basis of the seed size and weight revealed by the Chinese peanut key landraces - Juan Wang; Bingke Jiao; Chunjuan Qu; Caixia Yan; Dachuan Shi; Chen Jiang; Mei Yuan; Wenjiao Wang; Cuiling Yuan; Xiaobo Zhao; Quanxi Sun; Yifei Mou; et al. (Theoretical and Applied Genetics, 2025)

Inhalation risk assessment on 14 organic chemicals in children's masks based on the Monte Carlo stochastic modeling method - Yunbo Wang; Guixiao Li; Lihua Yu; Xiangke He; Xiaofeng Wei; Zhongxian Liu; Guiqin Zhang; Cuiling Gao (Atmospheric Pollution Research, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

A machine learning approach fusing multisource spectral data for prediction of floral origins and taste components of Apis cerana honey - Zhaolong Liu; Hongxia Li; Nan Liu; Cuiling Liu; Xiaorong Sun; Lanzhen Chen (Food Research International, 2025)

Spatial Heterogeneity of the Microbial Community in the Surface Sediments in the Okinawa Trough - Ye Chen; Nengyou Wu; Cuiling Xu; Youzhi Xin; Jing Li; Xilin Zhang; Yucheng Zhou; Zhilei Sun (Journal of Marine Science and Engineering, 2025)
The Okinawa Trough (OT) has been a focus of scientific research for many years due to the presence of vibrant hydrothermal and cold seep activity within its narrow basin. However, the spatial distribution and environmental drivers of microbial communities in OT sediments remain poorly understood. The present study aims to address this knowledge gap by investigating microbial diversity and abundance at ten different sampling sites in a transitional zone between hydrothermal vents and cold seeps in the OT. The microbial community at two sampling sites (G08 and G09) in close proximity to hydrothermal vents showed a high degree of similarity. However, lower bacterial and archaeal abundances were found in these sites. The archaeal groups, classified as Hydrothermarchaeota and Thermoplasmata, showed a comparatively higher relative abundance at these sites. In addition, ammonia-oxidizing archaea (AOA), from the family Nitrosopumilaceae, were found to have a higher relative abundance in the OT surface sediments at sampling sites G03, G04, G05, G06, and G07. This result suggests that ammonia oxidation may be actively occurring in these areas. Furthermore, Methylomirabilaceae, which are responsible for methane oxidation coupled with nitrite reduction, dominated three sampling sites (G07, G08, and G09), implying that N-DAMO may play an important role in mitigating methane emissions. Using the FAPROTAX database, we found that predicted prokaryotic microbial functional groups involved in methyl-reducing methanogenesis and hydrogenotrophic methanogenesis were most abundant at sites G08 and G09. At sampling sites G01 and G02, functional groups such as hydrocarbon degradation, methanotrophy, methanol oxidation, denitrification, sulfate respiration, and sulfur oxidation were more abundant. Nitrogen content is the most important environmental factor determining the bacterial and archaeal communities in the OT surface sediments. These results expand our knowledge of the spatial distribution of microbial communities in the transitional zone between hydrothermal vents and cold seeps in the OT.

Rapid and nondestructive identification of rice storage year using hyperspectral technology - Xiaorong Sun; Xinpeng Zhou; Cuiling Liu; Chunlin Li; Shanzhe Zhang; Dongyu Zheng (Food Control, 2025)

Identification of horse ingredients based on recombinase polymerase amplification, high-throughput DNA isolation and magnetic separation - Cuiling Li; Hangzhen Lan; Zhen Wu; Daodong Pan (Food Control, 2025)

ChatGPT-based meta-analysis for evaluating the temporal and spatial characteristics of deoxynivalenol contamination in Chinese wheat - Chuanzhi Jiang; Sen Li; Di Cai; Jin Ye; Qinghang Bao; Cuiling Liu; Songxue Wang (Journal of Hazardous Materials, 2024)

Pullulanase-assisted bamboo leaf flavonoids optimize the instant properties, in vitro digestibility, and underlying mechanism in yam flour - Zhenjiang Zhou; Ye Li; Minghao Xu; Shengyang Ji; Xi Zhao; Cuiling Zhu; Jianfu Shen; Xuan Yang; Baiyi Lu (Food Chemistry, 2024)

Status of river-connected lakes under the influence of the Three Gorges Dam: research progress and prospect - Jingtai Li; Li Chen; Cuiling Wu; Min Li; Dandan Yan; Siying Xie; Zhaoqing Luan (Ecohydrology & Hydrobiology, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Ordered porous copper sulfide with hollow interior for superior electrochemical CO2 to formate conversion - Wei Zhu; Longlong Fan; Qinghong Geng; Chengming Wang; Xiaoli Fan; Yingying Zhang; Cuiling Li (Chemical Engineering Journal, 2024)

Flexible human-machine interface touch system based on double-network solid-state ionic conductive elastomers - Wang Zhan; Qi Zhang; Zhilu Ye; Yuhao Wang; Zihao Yang; Yijing Wang; Cuiling Zhang; Zeying Zhang; Li Xue; Feng Ma; Zhiguang Wang; Niancai Peng; et al. (Chemical Engineering Journal, 2024)

Residual networks without pooling layers improve the accuracy of genomic predictions - Zhengchao Xie; Xiaogang Xu; Ling Li; Cuiling Wu; Yinxing Ma; Jingjing He; Sidi Wei; Jun Wang; Xianzhong Feng (Theoretical and Applied Genetics, 2024)

Comparison of four isothermal amplification techniques: LAMP, SEA, CPA, and RPA for the identification of chicken adulteration - Song Yan; Cuiling Li; Hangzhen Lan; Daodong Pan; Yichun Wu (Food Control, 2024)

Using organic fertilizer to mitigate organic-inorganic fouling in agricultural saline wastewater irrigation systems - Tahir Muhammad; Cuiling Jiang; Zeyuan Liu; Irum Manan; Yang Xiao; Yunkai Li (Chemosphere, 2024)

Geochemistry of iron and trace metals in seep carbonates of the middle Okinawa Trough impacted by hydrothermal plumes - Shuang-Shuang Qin; Mao-Xu Zhu; Tie Li; Xilin Zhang; Cuiling Xu; Hong Cao; Wei Geng; Bin Zhai; Ye Chen; Shixing Li; Zhilei Sun (Chemical Geology, 2024)

Impacts and mechanism of coal fly ash on kitchen waste composting performance: The perspective of microbial community - Tahir Muhammad; Cuiling Jiang; Yunkai Li; Irum Manan; Changjian Ma; Hui Geng; Iza Fatima; Muhammad Adnan (Chemosphere, 2024)

Red Emission Carbon Nanoparticles Which Can Simultaneously Responding to Hypochlorite and pH - Yinghua Liu; Wenxiu Duan; Huiqing Li; Jiang Wu; Dan Liu; Jiaying Mi; Shengda Qi; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2023)

Tectonic evolution of the Gubei sag with multiple boundary faults in the Bohai Bay Basin, East China and the control of tectonics over paleo-structures and hydrocarbons: Insights from three-dimensional reconstructions - Baogang Li; Cuiling Yu; Yuehan Zhao; Yunyun Wu; Ye Xin; Yuxin Guo (Journal of Asian Earth Sciences, 2023)

Ordered macroporous carbonous skeletons implanted with dual-phase Co/CoFe nanoparticles for boosting electrocatalytic performance - Jun-Xuan Li; Longlong Fan; Qingfeng Hua; Qinghong Geng; Yingying Zhang; Xiaoli Fan; Lian Ma; Chengming Wang; Wei Zhu; Xiao Feng; Cuiling Li (Chemical Engineering Journal, 2023)

Methane distribution and sea-to-air methane flux in the Dongsha area of the South China Sea - Cuiling Xu; Zhilei Sun; Qing Li; Xianrong Zhang; Xilin Zhang; Bin Zhai; Qiang Fu; Yuhai Sun; Wei Geng; Hong Cao; Ye Chen; Nengyou Wu (Continental Shelf Research, 2023)

NAC1 regulates root ground tissue maturation by coordinating with the SCR/SHR–CYCD6;1 module in Arabidopsis - Chuantian Xie; Cuiling Li; Fengxia Wang; Feng Zhang; Jiajia Liu; Junxia Wang; Xiansheng Zhang; Xiangpei Kong; Zhaojun Ding (Molecular Plant, 2023)

Stable isotope and elemental profiles determine geographical origin of saffron from China and Iran - Jing Nie; Jian Yang; Cuiling Liu; Chunlin Li; Shengzhi Shao; Chunxia Yao; Bilian Chen; Yi Tao; Fang Wang; Yongzhi Zhang; Karyne M. Rogers; Ping Wang; et al. (Food Chemistry, 2023)

Recent advances in Chinese food authentication and origin verification using isotope ratio mass spectrometry - Chunlin Li; Xuming Kang; Jing Nie; An Li; Mohamed A. Farag; Cuiling Liu; Karyne M. Rogers; Jianbo Xiao; Yuwei Yuan (Food Chemistry, 2023)

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

Ochratoxin A induces nephrotoxicity in vitro and in vivo via pyroptosis - Hu Li; Xinru Mao; Kai Liu; Jiahao Sun; Benrui Li; Rahmani Mohammad Malyar; Dandan Liu; Cuiling Pan; Fang Gan; Yunhuan Liu; Kehe Huang; Xingxiang Chen (Archives of Toxicology, 2021)

Decylubiquinone suppresses breast cancer growth and metastasis by inhibiting angiogenesis via the ROS/p53/ BAI1 signaling pathway - Jinghua Cao; Xiaohua Liu; Yang Yang; Bo Wei; Qianming Li; Guanquan Mao; Yajun He; Yuanyuan Li; Lingyun Zheng; Qianqian Zhang; Jiangchao Li; Lijing Wang; et al. (Angiogenesis, 2020)

Isolation and characterization of a novel seed-specific promoter from peanut (Arachis hypogaea L.) - Cuiling Yuan; Chunjuan Li; Caixia Yan; Xiaobo Zhao; Juan Wang; Quanxi Sun; Shihua Shan (Molecular Biology Reports, 2019)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Fertile introgression products generated via somatic hybridization between wheat and Thinopyrum intermedium - Cuiling Li; Aixia Cheng; Minqin Wang; Guangmin Xia (Plant Cell Reports, 2014)

Enhanced expression of the human CD14 protein in tobacco using a 22-kDa alpha-zein signal peptide - Xiuxia Liu; Li Sun; Cuiling Li; Aifang Yang; Juren Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Regeneration of asymmetric somatic hybrid plants from the fusion of two types of wheat with Russian wildrye - Cuiling Li; Guangmin Xia; Fengning Xiang; Chuanen Zhou; Aixia Cheng (Plant Cell Reports, 2004)

Fibroblast growth factor receptors (FGFRs) and their roles in limb development - Xiaoling Xu; Michael Weinstein; Cuiling Li; C.-X. Deng (Cell and Tissue Research, 1999)